Action of nurses in the organ removal team - Amorim, Josely Santana do; Silva, Giovani Carmo da; Assis, Ludmila Helena de (Brazilian Journal of Transplantation, 2011)
The organ donation process poses a set of systematic procedures including identification of potential donor until the transplantation is per- formed in the receiver. The removal of solid organs is one of the complex donation processes and requires a qualified and competent mul- tidisciplinary team to perform it. Among the health professional team, nursing has an active role, but there are few studies demonstrating the real importance of this professional inserted in the organ removal. : To know the functions of the nursing member within the solid organ removal team. Method: It was chosen the qualitative and descriptive research by conducting interviews that allowed us to survey the roles, attitudes and knowledge of a particular function. The study was conducted after approved by the Ethics and Research Committee of UFMG, according to the following criteria for inclusion: being a nurse with or without expertise in the transplantation area, and being a member of a solid organ removal team. Results: The study was attended by five nurses that fulfilled the inclusion criteria. In the data analysis, four categories emerged: responsibility by medical and surgical equipment to be transported; coordination and preparation of the operating room along the surgery, assessment and checking of the donor’s documentation required by law, and the organs perfusion and packaging of removed organs. Discussion: This confirms that nurses must have knowledge and control activities carried out within the surgical room by providing the preparation of the operating room, surgical and specific materials necessary for the procedure. This activity includes working in the whole removal process of each organ, added to activities of administrative and assistance feature in the organ removal process. Conclusion: It was evident that the nursing member of the solid organs removal team is active in this institution in the intra-operative pro- cess that includes caring and management activities within the surgical room.